CARDIAC RISK IN THE AGRO INDUSTRY WORKERS AND RURAL WORKERS: PROFILE OF MUNICIPALITIES IN SOUTHERN BRAZIL (Fiep Bulletin - online, 2014)
Studies on cardiovascular risks among workers are scarce even though this study is particularly important for the adoption of preventive measures. Assessment tool based on lifestyle variables, the Cardiac Risk Index (RISKO) focus on the following factors: total cholesterol, body weight, work and sports activities, smoking and blood pressure at rest, in addition to gender and heredity. The present study aims to characterize in workers of the agribusiness and rural workers the level of present cardiac risks, establishing associations among gender, age and place of residence of the subjects. This is an observational, descriptive study with 73 workers of four cities in the South of Brazil, using questionnaires about lifestyle, anthropometric, cardiorespiratory and biochemical evaluations. In RISKO the variables scored generate a sum and a risk classification: remote, below average, medium, moderate and high. Statistical analysis was performed using the SPSS software, using descriptive statistics of frequency and percentage. The subjects of the study were 64.4% female with average age of 50.76 (DP 11.78). For both genders the predominant risk score was “medium” (69.9%), with 76.9% for men and 66.0% for women. The municipality of Vale Verde had 93.8% of workers classified in a negative way regarding the health (index “medium” and “moderate”), followed by Passo do Sobrado (87.6%), Candelária (86.3%) and Santa Cruz do Sul (84.2%). It is possible to observe a considerable number of subjects with unfavorable health ratings, suggesting the need of preventive actions for health information to be developed with this population, especially because the score RISKO considers the lifestyle factors which are modifiable.
Keywords: cardiac risk; worker health; rural worker